LRRK2 Mutations and Asian Disease-Associated Variants in the First Parkinson's Disease Cohort from Kazakhstan. (19th February 2020) - Kaiyrzhanov, Rauan; Aitkulova, Akbota; Shashkin, Chingiz; Zharkinbekova, Nazira; Rizig, Mie; Zholdybayeva, Elena; Jarmukhanov, Zharkyn; Akhmetzhanov, Vadim; Kaishibayeva, Gulnaz; Khaibullin, Talgat; Karimova, Altynay; Akshulakov, Serik; et al.
Abstract : Background . LRRK2 mutations have emerged as the most prevalent and potentially treatable determinants of Parkinson's disease (PD). Peculiar geographic distribution of these mutations has triggered an interest in genotyping PD cohorts of different ethnic backgrounds for LRRK. Objective . Here, we report on the results of LRRK2 screening in the first Central Asian PD cohort. Methods . 246 PD patients were consecutively recruited by movement disorder specialists from four medical centers in Kazakhstan, and clinicodemographic data and genomic DNA from blood were systematically obtained and shipped to the Institute of Neurology University College London together with DNAs from 200 healthy controls. The cohort was genotyped for five LRRK2 mutations (p.Gly2019Ser, p.Arg1441His, p.Tyr1699Cys, p.Ile2020Thr, and p.Asn1437His) and three East Asian disease-associated variants (p.Gly2385Arg, p.Ala419Val, and p.Arg1628Pro) via Kompetitive allele-specific polymerase chain reaction assay analysis. Results . None of the study subjects carried LRRK2 mutations, whereas the following Asian variants were found with insignificant odds ratios (OR): p.Gly2385Arg (1.2%, minor allele frequency (MAF) 0.007, OR 1.25, p = 0.8 ), p.Ala419Val (3.7%, MAF 0.02, OR 1.5, p = 0.4 ), and p.Arg1628Pro was found only in 1% of controls. p.Gly2385Arg was positive in a big family with PD and tremor, although with incomplete segregation. One early-onset PD subject was homozygous for p.Ala419Val who developed fast progression and severe dyskinesias. p.Ala419Val was associated with early-onset PD. Conclusions . We showed that East Asian LRRK variants could be found in Central Asian populations but their pathogenicity remains to be elucidated in larger PD cohorts.